TRANSITIVITAS PANGIWA TEKS AJI BLEGODAWA - RASNA, I WAYAN (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): September 2010, 2010)
This article investigates the transitivity of Pangiwa (black magic) of Aji Bl?godawa text. The study was conducted by using Functional Systemic Linguistics. The data were analyzed by document recording method following the procedures : (1) classification of Aji Bl?godawa text based on similarity of content, (2) modification of the text, (3) analysis by using the functional systemic linguistics model (Halliday, 1985, 2004, 2005 ; Halliday and Matthiessen, 2004). The results showed that material process totaled 553 (48.47%) or ranked first. The second ranking went to relational process, with the total of 175 (20.42%). The third ranking was occupied by mental process with the total of 147 (15.70%). In the light the findings, as a procedural text, Aji Bl?godawa text necessitates the presence of action as the procedure in realizing the transitivity of procedural text.
Keywords: transitivity, Aji Blegodawa